Spectra of atoms and molecules - Bernath, Peter F. (Oxford University Press, 2020)
"This book is designed as a textbook to introduce advanced undergraduates and, particularly, new graduate students to the vast field of spectroscopy. It presumes that the student is familiar with the material in an undergraduate course in quantum mechanics. I have taken great care to review the relevant mathematics and quantum mechanics as needed throughout the book. Considerable detail is provided on the origin of spectroscopic principles. My goal is to demystify spectroscopy by showing the necessary steps in a derivation, as appropriate in a textbook. The digital computer has permeated all of science including spectroscopy. The application of simple analytical formulas and the nonstatistical graphical treatment of data are long dead. Modern spectroscopy is based on the matrix approach to quantum mechanics. Real spectroscopic problems can be solved on the computer more easily if they are formulated in terms of matrix operations rather than differential equations. I have tried to convey the spirit of modern spectroscopy, through the extensive use of the language of matrices"--